2020
DOI: 10.21203/rs.3.rs-135606/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ITPR3 Facilitates Tumor Growth, Metastasis and Stemness by Inducing the NF-ĸB/CD44 Pathway in Urinary Bladder Carcinoma

Abstract: Background: Bladder carcinoma is one of the most common urological cancers. ITPR3, as a ubiquitous endoplasmic reticulum calcium channel protein, was reported to be involved in the development and progression of various types of cancer. However, the potential roles and molecular mechanism of ITPR3 in bladder cancer are still unclear. Herein, we elucidated a novel role of ITPR3 in regulating the proliferation, metastasis, and stemness of bladder cancer cells.Methods: The expression of ITPR3 in bladder cancer wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…We found that migration ability was significantly suppressed in si-circIFT80 cells compared with si-NC cells, while on the migration capacity of CRC cells overexpressing circIFT80 was significantly higher than that of negative control cells (Figures 3(a) and 3(b)). MMP2 and MMP9, as the two most important members of the matrix metalloproteinases, play a crucial role in promoting cancer metastasis [14]. We found that the MMP2 and MMP9 protein levels were suppressed in HT-29 cells and SW480 cells after circIFT80 was knocked down.…”
Section: Circift80 Facilitated the Ability Of Crc Cells To Migratementioning
confidence: 79%
“…We found that migration ability was significantly suppressed in si-circIFT80 cells compared with si-NC cells, while on the migration capacity of CRC cells overexpressing circIFT80 was significantly higher than that of negative control cells (Figures 3(a) and 3(b)). MMP2 and MMP9, as the two most important members of the matrix metalloproteinases, play a crucial role in promoting cancer metastasis [14]. We found that the MMP2 and MMP9 protein levels were suppressed in HT-29 cells and SW480 cells after circIFT80 was knocked down.…”
Section: Circift80 Facilitated the Ability Of Crc Cells To Migratementioning
confidence: 79%
“…17 ITPR3 can also induce nuclear factor-kappa B/CD44 pathway signaling in urinary bladder carcinoma, thereby promoting tumor growth, stemlike behavior, and metastatic growth. 18 Increases in the expression of ITPR3 in hepatocellular carcinoma and colon cancer have also been linked to increased apoptotic activity and worse survival outcomes. 19,20 ITPR3 downregulation can suppress the migratory activity of breast cancer cells via oscillatory Ca 2+ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…ITPR3 degradation in prostate cancer has been found to be associated with PTEN mutations, disrupting the ability of FBXL2 to bind to ITPR3 and thereby promote its degradation, thus suppressing mitochondrial Ca 2+ signaling within tumor cells, increasing their apoptotic sensitivity 17 . ITPR3 can also induce nuclear factor‐kappa B/CD44 pathway signaling in urinary bladder carcinoma, thereby promoting tumor growth, stem‐like behavior, and metastatic growth 18 . Increases in the expression of ITPR3 in hepatocellular carcinoma and colon cancer have also been linked to increased apoptotic activity and worse survival outcomes 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HKid-CRCC060PG-01) was purchased from Outdo Biotech Co., Ltd. (Shanghai, China) including 30 ccRCC tissues and corresponding adjacent noncancerous tissues. The tissue chip was subjected to the immunohistochemistry staining assay according to the protocol previously described in this research [22]. Especially, the primary antibody was purchased from Abcam (anti-GTSE1,1:500) (ab272670).…”
Section: Ccrcc Tissue Chip and Immunohistochemistry (Ihc) Assaysmentioning
confidence: 99%